Pendampingan Peningkatan Santripreneur Dengan Penerapan Marketing Mix Produk Buket Batik di Pondok Modern Al-Ghuroba Kabupaten Sorong - Rokhimah Rokhimah; Susetyowati Sofia; Digor Mufti; Multin Multin; Febrianti Keliandan; Nurbaya Muhammad; Nisaleha Rumau; Nurul Qomariah (Universitas 45 Surabaya, 2023)
Butek batik is the result of using patchwork waste by creatively utilizing patchwork waste. A batik bouquet is a flower arrangement made from patchwork waste with batik motifs and has high artistic value. Flower bouquet products are popular with young people because they can be used as birthday gifts, graduation souvenirs and so on. During service activities, the marketing team conveys marketing materials. Marketing Mix refers to a series of strategies used in promoting batik bouquet products. The activity aims to provide guidance to the female students of Pondok Modern Al-Ghuroba to find out the application of marketing mix to products, thereby influencing purchasing decisions for Flower Bouquet products. This service method begins with observation, licensing, carrying out activities, discussions, strengthening materials. Based on the implementation of the activities carried out, it shows the importance of implementing a marketing mix for developing a business so that the products sold can be well received by the determined target market. The product is named Boutique and given a logo, the marketing team sets the price for a batik bouquet no different from the market price, the marketing team determines the use of Instagram for distribution, and the marketing team uses the facilities available on Instagram to promote the product so that it is better known to a wider market reach. The results of service activities at Pondok Modern Al-Ghuroba were carried out well as shown by the level of participation of the participants.